The Effectiveness of Problem Based Learning on Students' Ability to Think Critically - Abidin, Zaenal; Sulaiman, Fauziah (Zabags International Journal of Education, 2024)
This research aims to describe the effectiveness of implementing problem-based learning in an effort to develop students' critical thinking abilities. One of the advantages of the problem-based learning model is that it is able to train students to use various concepts, principles, and skills that they have learned to solve the problems they are facing. this study is a descriptive qualitative approach; this approach is expected to produce in-depth interviews and descriptions of speech, writing, and behavior that can be observed from an individual, group, society, and organizational unit of analysis. Next, according to the observed context, the data obtained is then recorded and analyzed. The results of this research are that students' critical thinking skills can develop, because the essential skills of thinking observed in this research are the ability to identify, analyze, solve problems, think logically, make appropriate decisions, are not easily provoked, and can draw conclusions carefully.